TiO2 nanoparticle dispersed porous gel polymer electrolyte membrane for room temperature Na-S battery. (2020) - Verma, Harshlata; Mishra, Kuldeep; Rai, D.K.
Abstract: Room temperature sodium-sulfur (Na-S) batteries are promising energy storage devices for meeting increasing energy demands. An electrolyte with reasonably high ionic conductivity (≥10 −4 S cm −1 ) is one of the key requirements for room temperature Na-S batteries. In this work, a sodium ion conducting flexible porous gel polymer electrolyte membrane of TiO2 (Titanium dioxide) dispersed Poly(vinylidene fluoride-hexafluoropropylene) soaked in a liquid electrolyte of NaPF6 (sodium hexafluorophosphate) in EC (ethylene carbonate): PC (Propylene carbonate) has been prepared. The electrolyte is obtained through phase inversion method and shows an ionic conductivity of 1.3 × 10 −3 S cm −1 . A proto-type Na-S battery has been fabricated and characterized using the prepared electrolyte membrane. The battery shows an open circuit voltage of ∼2.1 V and discharge capacity of 231 mA h g −1 . However, battery shows capacity fading during charge-discharge cycle.